1999
DOI: 10.1016/s0893-133x(98)00097-9
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation of Rat Medial Prefrontal Cortex Enhances Forebrain Serotonin Output Implications for Electroconvulsive Therapy and Transcranial Magnetic Stimulation in Depression

Abstract: Decreased activity of the prefrontal cortex (PFC), as well as reduced serotonergic neurotransmission, is considered as a characteristic feature of major depression. The mechanism by which electroconvulsive therapy (ECT) and transcranial magnetic stimulation (TMS) achieve their antidepressant effects may involve changes in PFC activity. It is, however, still unclear whether these changes are accompanied by increased synaptic availability of serotonin (5-HT). In the present study, 5-HT efflux in the rat ventral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(59 citation statements)
references
References 61 publications
5
52
0
2
Order By: Relevance
“…Convergent with results shown here, limbic 5-HT was enhanced after electrical stimulation of the mPFC but not of the latPFC (Juckel et al, 1999). Indeed, transecting mPFC efferents to the DR abolished the response of all recorded DR 5-HT neurons to the excitatory dose of WIN55,212-2.…”
Section: Discussionsupporting
confidence: 88%
“…Convergent with results shown here, limbic 5-HT was enhanced after electrical stimulation of the mPFC but not of the latPFC (Juckel et al, 1999). Indeed, transecting mPFC efferents to the DR abolished the response of all recorded DR 5-HT neurons to the excitatory dose of WIN55,212-2.…”
Section: Discussionsupporting
confidence: 88%
“…This includes a connection from the prefrontal cortex to the hippocampus. Furthermore, prefrontal stimulation has been shown to produce an increase in serotonin (5-HT) in the hippocampus (Groenewegen et al, 1997;Juckel et al, 1999). Interestingly, LTG has been shown to inhibit the uptake of serotonin, norepinephrine, and dopamine by rat cortical synaptosomes in vitro (Southam et al, 1998), although changes in monoamine levels could not be observed in vivo (Xie and Hagan, 1998).…”
Section: What Might This Study Tell Us About Ltg's Mechanism Of Actiomentioning
confidence: 99%
“…A1-receptor 5-HT2A, decrease in sensitivity, (Plein and bark, 2000) Activation of 5-HT and DA transmission, Yoshida et al (1998), Juckel et al (1999); stim. of 5-HT in hippocampus and amygdala via medial prefrontal cortex Imaging techniques Nobler et al, 2001; Selected areas decreased after ECT, i.e.…”
Section: Neurotrophic Factorsfcell Growth and Neuroplasticitymentioning
confidence: 99%
“…McGarvey et al (1993) demonstrated that ECS-induced dopamine release depended on the effects of electrode placements and stimulus intensity. Juckel et al (1999) demonstrated that electrical stimulation on medial prefrontal cortex (PFC) produced currentdependent increases in limbic 5-HT output in both urethane-anesthetized and behaving rats. They concluded that this pronounced regional specificity of the medial PFC stimulation on limbic 5-HT output suggests that activation of this particular area might play a crucial role in such antidepressant treatment as ECT and trans-magnetic stimulation.…”
Section: Brain Neurotransmitters and Their Receptorsmentioning
confidence: 99%